Enhancing Broiler Growth Performance and Gut Health: A Comparative Study on the Impact of Probiotics, Prebiotics, and Pomegranate (Punica granatum L.) Peel Powder - M Shams Shargh; O Ashayerizadeh; MH Mohammadi; SG Shirangi (Brazilian Journal of Poultry Science)
ABSTRACT A total of 200 one-day-old Ross 308 male broilers were randomly assigned to 4 treatments and 5 replicates in a completely randomized design to assess growth performance, serum biochemicals, and intestinal characteristics for 42 days. Treatments comprised Control (C), probiotic, prebiotic and pomegranate peel powder (PPP). The results showed that birds fed probiotic had higher average daily feed intake (ADFI) and average daily gain (ADG) compared to the C and prebiotic groups from day 1 to 42 (p<0.05). Adding PPP improved ADFI (+2.73%) and ADG (+3.16%) compared to the C and prebiotic groups from day 1 to 42. Adding probiotic, prebiotic and PPP significantly reduced and increased feed conversion ratio (FCR) in the grower and finisher periods in comparison to C, respectively. Moreover, probiotic, prebiotic and PPP had no significant effect on FCR from day 1 to 42. Birds fed probiotic had higher villus height (VH) and lower crypt depth (CD) of the duodenum than those from other treatments (p<0.05). Birds fed probiotic and prebiotic diets had numerically lower villus surface area (VSA) in the duodenum than those in the C treatment. Probiotic supplementation enhanced the VSA in the jejunum compared to the PPP and C treatments (p<0.05). Superoxide dismutase (SOD) activity of serum increased in the probiotic and prebiotic-fed birds, but not in PPP ones (p<0.05). Probiotic, prebiotic and PPP declined serum malondialdehyde (MDA) levels in comparison to the C treatment (p<0.05). Overall, probiotic and PPP inclusion in diets improved the growth performance of broiler chicks.